Implementation Sanitation Standard Operational Procedure in Online Food during Covid-19 Pandemic in East Jakarta - Ridawati Ridawati; Alsuhendra Alsuhendra (International Journal of Research in Community Services, 2022)
The COVID-19 pandemic has caused people to immobilize to eat out, many industries are closed, the community’s economy is down, and many online food small and medium enterprises (SMEs) have sprung up. One of the areas affected by the COVID-19 pandemic is East Jakarta. The implementation of Sanitation Standard Operational Procedure (SSOP) in online food SMEs requires special attention during the COVID-19 pandemic. This study aims to evaluate food production facilities in online food SMEs. Direct observation using instrument from Indonesian National Agency of Drug and Food Control (BPOM) Number HK.03.1.23.04.12.2207 2012 was conducted. The survey was conducted from May to June 2021 in five sub-districts in East Jakarta, namely Duren Sawit, Matraman, Pulo Gadung, Kampung Makassar, and Cipayung.  Of the 32 SMEs observed, 50% had been established in less than one year. Most of the SMEs owners have secondary and higher education education and sell popular Street food or food.  The survey covers non-compliance in 14 elements of food production facilities. The results show minor disobedience 18.8%, major disobedience 33.3%, serious defiance 25.8%, and critical disobedience 29.9%. In conclusion, major disobedience had the highest percentage, followed by critical, serious, and minor disobedience. Further education in the application of SSOP for online food SMEs should be carried out.